The Impact of Financial, Economic and Environmental Factors on Energy Efficiency, Intensity, and Dependence: The Moderating Role of Governance and Institutional Quality - Ijaz, Syeda Tayyaba; Chughtai, Sumayya (International Journal of Energy Economics and Policy, 2022)
Economies are under serious pressure to sustain themselves due to globalization, focusing simply on economic growth and operational efficiency will not yield the desired sustainable financial and economic position for economies. Management of energy efficiency and reducing the energy dependence and intensity is the core objective for the economy and achievement of the above objective financial, economic, and environmental factors need to be studied. Economic wellbeing critically depends on the efficient use of energy and which type of governance mechanism is in place will also define the ways toward energy efficiency. A better understanding of the relationship will help the economies to fulfill their energy needs efficiently, realize developmental goals, and overcome environmental issues. This study examines the relationship between financial, economic, and environmental factors with energy efficiency, intensity, and dependency with moderating role of governance including institutional quality and governance index for belt and road initiative countries. The core objective of the study is to analyze which financial, economic, and environmental factors serve well in the management of energy efficiency, intensity, and dependence issues and how various dynamics of governance policies including market structure moderate the above-mentioned relationship. For this secondary data is used from world development indicators, market insiders, and Chicago Board Options Exchange (CBOE) data. This research will help the researchers and practitioners to achieve long-term economic, financial, and environmental sustainability. The proposed model predicts that 0.44% change in Total Factor Energy Productivity measure of Energy Efficiency, 0.03% changes in Energy use/Purchasing Power Parity ratio measure of Energy Intensity, and 9.63% changes in Energy Reserves/Energy Production ratio measure of Energy Dependence. Results also reveal that environmental factors including Rural population, Urbanization, Co2 emission, energy use, and energy production will contribute most to achieving sustainable economic growth.